The exploration of biochemistry laboratory activity: Study on higher education in Mataram - Anwar, Yunita Arian Sani; Muti'ah, Muti'ah (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2023)
As the core of science learning, laboratory work is inseparable from learning chemistry, including biochemistry. However, the implementation of laboratory work needs reconstruction, especially in higher education, so an initial study is needed to understand the problems in laboratory work at universities. This article was a study of the working conditions of the biochemistry laboratory at the University of Mataram. This study included quantitative research with students (N = 250), lab work assistants (N = 36), laboratorium staff (N = 4), and biochemistry lecturers (N = 4) as respondents. Techniques for obtaining data through participatory observation and questionnaires. Supporting data were obtained through interviews with students, lecturers, laboratory assistants, and laboratory personnel representatives. The results showed that the implementation of biochemistry lab work at the University in Mataram had gone through the pre-laboratory, laboratory work, and post-laboratory stages. Expository, inquiry, and demonstration are lab work methods, with 80% of the implementation using the expository method. Instructions related to waste handling have not been carried out in the implementation of biochemistry lab work. Based on these findings, several recommendations were put forward for improving the biochemistry lab work at the University.